Impact of educational interventions on the prevention of emerging diseases: A systematic review - Ahmady, Soleiman; Habibi, Amin; Massoudi, Nilofar (Novelty in Biomedicine, 2022)
Background: Seasonal influenza and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) could cause considerable morbidity and mortality. The present study investigates the effectiveness of educational interventions to prevent these diseases. Materials and Methods: We searched PubMed/Medline, Embase, and Cochrane Controlled Register of Trials (CENTRAL) for relevant clinical studies up to March 25, 2022. The following terms were used: “influenza”, “flu”, “respiratory infection”, “prevent”, "severe acute respiratory syndrome", COVID-19 “intervention”, “education”, “school-based”, and “inform”. Results: Out of 1296 studies retrieved from databases, 13 types of clinical trials met the inclusion criteria and were included in the study. E-learning and the educational module were the most common interventions for influenza and COVID-19, respectively. The measured outcomes were health promotion strategies and preventive behaviors among participants. All except one article showed a significant association between educational interventions and outcomes. Conclusion: The included studies in the current systematic review indicated the efficacy of health promotion educational interventions in improving knowledge and preventive behaviors regarding COVID-19 and Influenza.